Collaborative Care Models In Radiology: Integrating Nursing Expertise For Improved Outcomes (Journal of Namibian Studies : History Politics Culture, 2023)
Collaborative care models in radiology have gained recognition as essential frameworks for optimizing patient outcomes and enhancing the quality of healthcare delivery. This article explores the integration of nursing expertise within radiology departments to achieve improved patient care and diagnostic accuracy. Drawing on interdisciplinary collaboration, this paper examines the roles of radiology nurses in various imaging modalities, procedural assistance, patient education, and radiation safety protocols. Moreover, it highlights the significance of effective communication, shared decision-making, and teamwork in fostering a culture of collaboration within radiology settings. By leveraging nursing expertise alongside radiological technology, healthcare institutions can enhance efficiency, patient satisfaction, and clinical outcomes in diagnostic and interventional radiology procedures. This article aims to provide insights into the development and implementation of collaborative care models in radiology, emphasizing the synergistic relationship between nursing and radiological disciplines to optimize healthcare delivery.